Mother! I'm autistic. Am I a burden to you? - Chow, Heng Yee; Daud, Mohd Najmi; Wan Abdullah, Wan Arnidawati (Human Resource Management Academic Research Society, 2020)
Having children with Autism Spectrum Disorder (ASD) is a demanding undertaking, which requires high commitments from their caretakers. In response to this, this research was conducted to explore the lived experiences of low-income mothers with ASD children. This research is qualitative research, which utilized the Interpretative Phenomenological Analysis (IPA). Four participants were recruited for the present study, consisting of low-income mothers who have children with ASD and a monthly household income of less than MYR3000. All participants completed at least two semi-structured interviews and were recorded digitally, transcribed, analysed, and interpreted. The analysis showed that the participants perceived having ASD children as a challenge. They associated the challenges with mental preparation issues, difficulties in the career adjustments process, conflicts in child care, and the differences in parenting approaches. As an implication, understanding mothers' experiences with ASD children is crucial towards providing the necessary supports.